Improving the Quality of Education in Islamic Boarding School-Based Schools - Moh. Syafi’i; Lestari Widodo (Pascasarjana Universitas Qomaruddin, 2024)
BP Ma'arif NU Assa'adah Junior High School is one of the schools that organizes the Islamic Boarding School-Based (SBP) program. In 2009, the Education Office appointed BP Ma'arif NU Assa'adah Junior High School to organize the SBP program, citing the school's readiness and its status as an Islamic boarding school. The focus of this research is the implementation of pesantren-based school education at BP Ma'arif NU Assa'adah Bungah Gresik Junior High School and efforts to improve the quality of pesantren-based school education at BP Ma'arif NU Assa'adah Bungah Gresik Junior High School. This research is qualitative in nature and employs a case study approach. The data collection techniques used in this study are participant observation, unstructured in-depth interviews, and documentation. The study's results demonstrate the development of several aspects of the SBP program at BP Ma'arif NU Assa'adah Junior High School, including curriculum development, facility and infrastructure improvements, human resource (HR) enhancements for both teachers and educators, education personnel, and students, and the enhancement of religious (spiritual) activities. Meanwhile, the focus of efforts to enhance the quality of education through SBP is on developing the curriculum, enhancing the quality of students, and improving the quality of teachers. The theoretical implications show that the Islamic Boarding School-Based Program will be considered good if it is able to integrate the school education system with the Islamic boarding school education system well, which will ultimately create educational outputs with character.